A reflection on the negative side of crows in Malay proverbs: inquisitive semantics analysis [Refleksi sisi negatif burung gagak dalam peribahasa Melayu: analisis semantik inkuisitif] - Daud, Muhammad Zaid; Abdullah, Nurul Aida; Subet, Mary Fatimah (Universiti Malaysia Sarawak, 2021)
In the traditional Malay community, the crow is a symbol of ugliness, weakness, unfulfilled dreams, and difficult changes. This study explored the reasons for the symbolic use of crows in Malay proverbs using the Inquisitive Semantics Theory (Jalaluddin, 2014), as well as the Cross Reference Framework (Kempson, 1986). The proverbial data in this research was obtained by applying the purposive sampling method on three dictionaries: Kamus Peribahasa Melayu Edisi Kelima (Rahman, 2017), Kamus Istimewa Peribahasa Melayu Edisi Kedua (Hussain, 2016) and Kamus Peribahasa Melayu (Said, 2013). Nine Malay proverbs that mentioned “crows” were found. Despite recent studies proving that crows are intelligent birds; particularly in solving problems and expressing complex feelings, the Malay community’s perception of the crow remains negative. In this regard, this study re-evaluated in depth the Malays’ current and past views on crows.